THE ARAB INSRAELI MINORITY, THEIR SOCIOECONOMIC STATUS AND HOW THEY FACE INEQUALITY - Levnawi, Ayed Yousof (My University, 2016)
Since the establishment of the state of Israel and over the years The Arab minority struggles to cancel governance inequality, and to improve their socioeco-nomic status, by attempts to achieve their rights , according to the expression " rights are taken aren't given". The Israeli Arabs began to respond against discrimination, but it still so far to achieve quality, and it seems that this process just began.